2016
DOI: 10.1007/s15010-016-0944-5
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of multidrug-resistant Pseudomonas aeruginosa breakthrough bacteremia with ceftolozane/tazobactam

Abstract: We describe the use of off-label ceftolozane/tazobactam in the management of a multidrug-resistant Pseudomonas aeruginosa bacteremia that was already being treated with colistin and amikacin, the only active antibiotics according to the antibiogram.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 4 publications
2
22
0
Order By: Relevance
“…There are published data on the use of ceftolozane-tazobactam for the treatment of severe infections caused by MDR P. aeruginosa [119,[222][223][224][225].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…There are published data on the use of ceftolozane-tazobactam for the treatment of severe infections caused by MDR P. aeruginosa [119,[222][223][224][225].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…To overcome this problem, new antibiotics, such as ceftolozane-tazobactam (C-T), which can be an effective and safe alternative for the treatment of MDRPA infections (5,6), were recently developed. C-T is a new combination of an antipseudomonal cephalosporin and a beta-lactamase inhibitor.…”
mentioning
confidence: 99%
“…Eight studies reported that 57 patients with RTIs were admitted to the ICU. 16,21,29,32,34,35,39,45 The majority of these studies were either single patient case reports (6 studies), 21,29,32,34,35,39 or a case series comprising two patients. 16 One larger study -conducted in patients with RTIs onlyreported that 49 patients (of 62 recruited; 79.0%) were admitted to the ICU.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…44 Twelve studies reported 74 patients that were immunocompromised. 17,20,[25][26][27][28][29]39,40,42,43,45 Of these studies, two included only immunocompromised patients. 28,43 As with ICU patients, this is likely an underestimation as most multi-infection studies did not provide a breakdown by infection type.…”
Section: Study Characteristicsmentioning
confidence: 99%